ANALISIS PRODUK DARAH: KONTAMINASI BAKTERI PADA THROMBOCYTE CONCENTRATE - Serafica Btari Christiyani Kusumaningrum; Wiwit Sepvianti (Universitas Jenderal Achmad Yani Yogyakarta, 2018)
Background: Bacterial contamination in thrombocyte concentrate (TC) blood product becomes a serious problem since it can cause clinical risks from mild symptom to death. TC storage condition at 22-25oC with agitation is good condition for bacterial growth. Source of bacterial contamination can come from donor bacteremia, not aseptically from taking and processing blood product. In a previous study, showed there were positive gram bacteria as bacterial contamination in TC. Objective: This objective aims to determine bacterial contaminants in TC blood products. Methods: Total of 3 TC bag samples were collected from UDD PMI Kabupaten Sleman. Each sample was inoculated to nutrient agar media and it incubated for 48 jam at 37oC. Observation of bacterial colony growth is carried out after incubation time is over. Results: There was no bacterial growth in the media so that there was no bacterial contamination in TC. It showed that the procedures, processing, and storage of TC products in PMI Kabupaten Sleman were aseptic. Besides that, TC donors also did not suffer from bacteremia so there was bacterial contamination in TC. Conclusion: In this study, bacterial contamination in blood product TC was not found since there was no bacterial growth in media. Keywords: Bacterial contamination, blood products, blood bank, thrombocyte concentrate.